Studi tentang Minat Belajar pada Siswa Broken Home di SD Negeri 06 Pontianak Selatan - Debi Hanizar; Luhur Wicaksono; Yulie Yulie (Departement of Mathematics Education, 2024)
This study aims to find out the interests of students broken home SD State 06 Pontianak South. The method used is qualitative research in descriptive form. The source of the data in this study is a student from a broken home family. As for data collection techniques using observations, interviews, and documentation. Analysis of research data is presented qualitatively descriptively using two informants. The results of this study show that students from broken home families have had a negative impact on their learning interests and influence on the learning results achieved at school but there are also students from Broken Home families who do not experience it. The interests of students from broken home families vary. There are students who have a high interest in learning with shown enthusiasm in following the learning process and good learning outcomes and students with low learning interests showed a less enthusiast in following learning and getting less good learning expectations.